Labor Migration from Ukraine to the EU: an Analysis of Characteristics and Consequences - Bezrukova Nataliya V.; Svichkar Vitaliy A. (Bìznes Inform, 2016)
The article is aimed at analyzing characteristics of labor migration from Ukraine to the European Union and evaluating the possible consequences of this process, as well as determining the future development trends in terms of emigration from Ukraine. The main directions of labor migration from Ukraine have been examined. An estimation of the volume of labor migration has been provided. Data about the socio-demographic characteristics of migrants have been presented. It is specified that the process of emigration has both positive and negative consequences for our country. Particular attention is paid to the analysis of employment settings of migrants in the Member States of the European Union. The main causes of emigration from Ukraine, among which both unemployment and low wages, have been allocated. The authors prove that the average monthly salary of Ukrainian migrants in the EU Member States is much higher than in Ukraine. On the basis of the carried out study has been concluded that labor migration from Ukraine to the EU has important socio-economic importance to our State. At the same time, signing of the Association agreement between Ukraine, on the one hand, and the European Union, the European Atomic Energy Community and their Member States, on the other hand, as well as introduction of a visa-free regime, will contribute to an increase in the number of labor migrants.